Spherical catalyst components containing fluorinated ester electron donors, methods of preparation, catalysts and use in ethylene polymerization

CN117946304BActive Publication Date: 2026-10-13CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202211282137.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-19
Publication Date
2026-10-13
Estimated Expiration
2042-10-19

AI Technical Summary

Technical Problem

[0004]对于第一种技术,例如专利文献CN1099041A、CN1140722A等,先将氯化镁固体溶解,然后加入四氯化钛以及给电子体,通过缓慢改变合成条件析出催化剂颗粒,但是这种合成方法得到的催化剂颗粒形态不易控制,容易得到形貌不规则的催化剂,并且控制每一批次催化剂的形貌也变得非常困难

Benefits of technology

[0054]本发明的发明人通过研究验证,认为,本发明中的催化剂之所以具有上述的优势,原因在于:通过氟原子的强吸电子效应,极大地改变了催化剂活性中心的电子云密度。相比于其他卤素酯类化合物,氟原子的引入可以把吸电子性效应放到最大,极大地降低催化中心的电子云密度,进而调控催化剂的共聚性能,结合本发明中的其他特定的组成,得到了共聚性能好,粒径均匀、粒径分布窄的乙烯气相聚合催化剂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The application belongs to the field of catalysts, and discloses a fluorine-containing ester electron donor spherical catalyst component, a preparation method, a catalyst and application in ethylene polymerization. The electron donor catalyst component comprises the reaction products of the following components: ① a carrier, which is a magnesium alcoholate; ② a titanium-containing compound; optionally ③ an organic aluminum compound; and ④ an electron donor, which comprises an ether compound and a fluorine-containing ester compound. The spherical catalyst component has good copolymerization performance, the catalyst particles have regular shapes and are not easy to break, and the obtained polymer has less powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalysts, specifically relating to a spherical catalyst component containing a fluorinated ester electron donor, its preparation method, the catalyst itself, and its application in ethylene polymerization. Background Technology

[0002] Magnesium chloride (MgCl2) supported heterogeneous Zn catalysts (Ziegler-Natta type catalysts) play a crucial role in olefin polymerization and have been a focus of research in both academia and industry. The core of research on heterogeneous Zn catalysts lies in adjusting their polymerization activity, hydrogen sensitivity, copolymerization performance, and particle morphology and size distribution. Different supports, electron donors, and synthesis processes are typically selected to regulate hydrogen sensitivity, copolymerization, and particle morphology, resulting in various types of catalysts widely used in olefin polymerization. In the gas-phase fluidized bed polymerization of ethylene, maintaining suitable polymerization activity, copolymerization performance, and hydrogen sensitivity is essential, and the catalyst particle size and distribution are also critical, directly affecting the polymer particle size and size distribution. Producing polyethylene particles with good spherical size and suitable particle size can effectively improve product flowability and fluidized bed process operation, and has always been an important goal of catalyst synthesis in both science and industry.

[0003] Among the reported techniques for synthesizing catalysts with uniform particle size, there are mainly two types: the first type involves uniformly dispersing the various components of the catalyst in a solution and then obtaining the catalyst through sedimentation; the second type involves directly loading the active components of the catalyst onto an inert spherical support with good particle size.

[0004] For the first technology, such as patent documents CN1099041A and CN1140722A, magnesium chloride solid is first dissolved, and then titanium tetrachloride and an electron donor are added. Catalyst particles are precipitated by slowly changing the synthesis conditions. However, the morphology of the catalyst particles obtained by this synthesis method is not easy to control, and it is easy to obtain catalysts with irregular morphology. Furthermore, controlling the morphology of each batch of catalysts becomes very difficult.

[0005] The second technique involves loading the active component onto an inert support. For example, in patent CN1268520A, silica gel is used as the support. While silica gel particles are easy to control in diameter and have good morphology, and can produce catalysts with good sphericity and uniform particle size under specific synthesis processes, the loading capacity of the active component on this silica gel support is limited, resulting in lower polymerization activity. Patent US4293673A uses a composite support of silica gel and magnesium chloride to prepare a catalyst with better particle morphology, solving the problem of insufficient active component loading and greatly improving the catalytic activity. However, this synthesis process is relatively complex, posing certain difficulties for production.

[0006] In recent years, Sinopec Beijing Chemical Research Institute Co., Ltd. has successfully developed a heterogeneous Zn catalyst synthesized using magnesium chloride alkoxides as a support for propylene polymerization. This support boasts a simple synthesis process and features good spherical particle size and narrow particle size distribution. However, its application in ethylene polymerization is not yet mature, with only a few reports on the use of spherical magnesium alkoxide supports for gas-phase ethylene polymerization. Patents CN102020732A and CN102050897B describe the use of magnesium alkoxide supports for ethylene polymerization after de-alcoholization pretreatment with alkylaluminum and titanium tetrachloride, respectively. On the other hand, patent CN1118488C describes the introduction of haloalkanes into a titanium-containing catalyst system for ethylene polymerization, which not only significantly improves catalyst activity but also noticeably increases resin bulk density and improves polymer particle morphology to some extent. Patent CN102432712A utilizes the in-situ reaction of halocarboxylic acids with alcohols in magnesium alkoxide supports to generate haloesters as electron donors, reducing the amount of titanium tetrachloride used. The resulting catalyst exhibits high catalytic activity, good hydrogen sensitivity, and a narrow polymer distribution. However, the inventors of this invention discovered through research that the reaction between carboxylic acids and alcohols to form esters is an equilibrium reaction, and it is difficult to ensure that halocarboxylic acids are completely converted into haloesters. Furthermore, the haloester compounds used in this patent are polychlorinated esters, and the copolymerization performance of the catalyst in this document needs to be further improved.

[0007] Through further research, the inventors of this invention unexpectedly prepared an ethylene gas-phase polymerization catalyst with good copolymerization performance, uniform particle size, and narrow particle size distribution by using common ether compounds and fluorinated ester compounds as electron donors. The catalyst particles have regular shape, are not easily broken, and the resulting polymer powder is less and has a lower density. Summary of the Invention

[0008] To address the problems existing in the prior art and the discoveries of the inventors, the purpose of this invention is to provide a spherical catalyst composition, preparation method, catalyst, and application in the polymerization of olefins (e.g., ethylene) using fluorinated ester electron donors. Specifically, this invention relates to the preparation of a spherical catalyst for ethylene polymerization. The method uses magnesium halide ethanolate as a support and selects fluorine, the halogen with the smallest atomic radius and strongest electron-withdrawing ability, as a substituent. Specifically, fluorinated ester compounds and commonly used monoether compounds are used together as electron donors to prepare the spherical catalyst. This catalyst is suitable for both gas-phase polymerization and slurry polymerization processes of ethylene. The combination of monoether compounds and fluorinated ester compounds as electron donors, combined with the specific raw materials of this invention, results in a spherical catalyst with good copolymerization performance, regular particle shape, and less breakage, leading to less polymer powder.

[0009] The first aspect of the present invention is to provide a fluorinated ester-based electron donor catalyst component comprising the reaction product of the following components: ① a support, said support being a magnesium alkoxide compound; ② a titanium-containing compound; optionally ③ an organoaluminum compound; ④ an electron donor, said electron donor comprising an ether compound and a fluorinated ester compound.

[0010] According to the above technical solution, this invention provides a catalyst with good spherical particle size for ethylene polymerization and copolymerization. This catalyst uses ether compounds and fluorine-substituted ester compounds as electron donors. Through the combined effect of the fluorinated ester compounds and ether compounds, and the specific composition of this invention, the copolymerization performance of the catalyst is improved while maintaining good spherical particle size. The inventors of this invention believe that the strong electron-withdrawing property of fluorine atoms alters the electronic effect of the active center, enabling the catalyst with the above-mentioned specific composition to exhibit the aforementioned beneficial effects.

[0011] According to the present invention, the ether compound can be selected from a wide range, and in a preferred embodiment of the present invention, the ether compound is as shown in formula (1): In formula (1), R1 and R2 are non-substituted C1-C14 aliphatic or aromatic hydrocarbon groups; or, R1 and R2 are linked to form cyclic ethers and their derivatives; preferably, the ether compound is a monoether compound; more preferably, it is at least one of methyl ether, diethyl ether, n-propyl ether, isopropyl ether, n-butyl ether, methyl ethyl ether, methyl butyl ether, ethyl isopropyl ether, diethyl butyl ether, ethylene oxide, 1,2-epoxypropane, 1,2-epoxybutane, 2,3-epoxybutane, tetrahydrofuran, anisole, diphenyl ether, phenethyl ether, benzyl ether, benzyl methyl ether, benzyl ethyl ether, benzyl phenyl ether, and cyclopentane oxide.

[0012] According to the present invention, the fluorinated ester compounds can be selected from a wide range. In a preferred embodiment of the present invention, the fluorinated ester compounds include simple fluorinated ester compounds and / or fluorinated ester compounds in which fluorine is substituted with other elements.

[0013] Fluorinated esters are compounds in which only fluorine, a halogen element, is substituted. Fluorinated esters, on the other hand, are compounds in which fluorine is substituted not only with fluorine but also with other elements besides fluorine. For example, fluorinated esters are primarily fluorinated esters, including those in which fluorine is substituted with other halogen elements.

[0014] Fluorinated esters are mainly fluorinated esters, which are further divided into aliphatic fluorinated esters, aromatic fluorinated esters, and fluoroalkyl acid esters.

[0015] Preferably, the fluorinated ester compound includes at least one of the following compounds:

[0016] Aliphatic fluorinated esters represented by formula (2), aromatic fluorinated esters represented by formula (3), and fluoroalkyl acid esters represented by formula (4) and / or formula (5);

[0017] In formula (2), groups R1 and R2 may be the same or different, and each may be H, F, Cl, Br, I, substituted or unsubstituted phenyl, C1-C 14 Alkyl or fluoroalkyl; R3 is C1-C 14 The aliphatic or aromatic hydrocarbon group; preferably fluorinated aliphatic esters, preferably ethyl fluoroacetate, ethyl difluoroacetate, ethyl trifluoroacetate, ethyl fluorochloroacetate, ethyl fluorobromoacetate, ethyl 2-bromotetrafluoropropionate, ethyl difluoroiodoacetate, ethyl pentafluoropropionate, ethyl 2,2-difluoro-2-(4-methoxyphenyl)acetate, ethyl 2-(3,4-difluorophenyl)-2,2-difluoroacetate, ethyl 2-(2-cyanophenyl)-2,2-difluoroacetate, or a mixture thereof;

[0018] Mode In formula (3), R1, R2, R3, R4, and R5 are respectively H, F, Cl, Br, I, CF3, NH2, NO2, CN, or Cl-C 14 The alkyl group, wherein at least one of R1, R2, R3, R4, and R5 is F or CF3; R6 is C1-C 14 The aliphatic or aromatic hydrocarbon group; preferably, one or a mixture thereof, of ethyl pentafluorobenzoate, ethyl 3-fluoro-4-(trifluoromethyl)benzoate, ethyl 3-fluoro-4-(trifluoromethoxy)benzoate, ethyl 2,3,4,5-tetrafluorobenzoate, ethyl 2,4,5-trifluorobenzoate, ethyl 2,3-difluorobenzoate, ethyl 2,5-difluorobenzoate, ethyl 3-fluorobenzoate, ethyl 3-fluoro-4-nitrobenzoate, and ethyl 3-fluoro-4-cyanobenzoate;

[0019] In formulas (4) and (5), R1, R2, and R3 are each H, F, CH3, CF3, or one of alkyl, olefinic, or aromatic groups with fewer than 14 carbon atoms.

[0020] In equations (4) and (5), R4 and R5 are respectively H, F, Cl, Br, I, CF3, and Cl-C. 14 Alkyl or halogen-substituted C1-C 14Alkyl or aromatic groups. Preferably, one or more of the following: ethyl 2,2,2-trifluoroethyl ester, ethyl 2,2-difluoroethyl ester, 2,2,2-trifluoroethyl butyrate, 2,2,2-trifluoroethyl trifluoroethyl ester, bis(2,2,2-trifluoroethyl) phthalate, 2,2,2-trifluoroethyl acrylate, trifluoroethyl methacrylate, heptafluoroisopropyl acrylate, 2,2,3,3,3-pentafluoropropyl acrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, 2,2,3,3-tetrafluoropropyl methacrylate, hexafluorobutyl methacrylate, 2,2,3,3,4,4,4-heptafluorobutyl acrylate, 2,2,3,3,4,4,4-heptafluorobutyl methacrylate, and pentafluoropropyl acrylate.

[0021] The electron donors used in this invention include ether compounds and fluorinated ester compounds. The molar ratio of the ether compounds and fluorinated ester compounds under normal conditions is in the range of 1:99-90:10, preferably in the range of 10:90-60:40, and the optimal ratio is 35:65.

[0022] According to the present invention, the magnesium alkoxide compound may be a magnesium alkoxide compound commonly used in the art in the prior art. In a preferred embodiment of the present invention, the magnesium alkoxide compound is spherical particles; and / or,

[0023] The molar ratio of alcohol to magnesium in the magnesium alkoxide compound is (0.2-3.6):1; and / or, the alcohol in the magnesium alkoxide compound is a low-carbon alcohol of C1-C4, preferably at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol and isobutanol; and / or, the magnesium source in the magnesium alkoxide compound is magnesium chloride.

[0024] According to the present invention, the above-mentioned magnesium alkoxide compound can be prepared by referring to the method described in patent CN1091748A: a lower carbon alcohol is mixed with anhydrous magnesium chloride in a molar ratio of 2:1 to 3.6:1, heated to melt, and reacted to form a magnesium chloride alkoxide melt. The melt is then rapidly stirred in a dispersant and rapidly cooled to obtain spherical magnesium chloride alkoxides. The alcohol includes methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, and other higher carbon aliphatic alcohols, preferably ethanol. The molar ratio of alcohol to magnesium chloride is 2.0-3.6.

[0025] In this paper, the magnesium alkoxide spherical supports used also include those with low alcohol content obtained by physical dealcoholization methods such as hot nitrogen purging or vacuum dealcoholization using a vacuum pump. Experiments have shown that supports prepared by physical dealcoholization methods with an alcohol-to-magnesium molar ratio in the range of 0.2-3.6 can be used to synthesize highly active spherical catalysts, with a preferred alcohol-to-magnesium molar ratio in the range of 0.9-2.6.

[0026] According to the present invention, the titanium-containing compound can be selected from a wide range. In a preferred embodiment of the present invention, the titanium-containing compound has the general formula Ti(OR). n X 3-n Or Ti(OR) m X 4-m Ti(OR) n X 3-n And Ti(OR) m X 4-m In the formula, R can be the same or different, and each is C1-C. 14 The titanium-containing compound is composed of an aliphatic or aromatic hydrocarbon group, where X is a halogen, 3-n and 4-m are positive integers, and n and m are zero or positive integers. The titanium-containing compound includes directly added alkoxy titanium halides, in-situ generated alkoxy titanium halides, and mixtures thereof. Preferably, it is one or a mixture of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetraethoxy, titanium monochlorotriethoxy, titanium dichlorodiethoxy, titanium trichloromonethoxy, and titanium trichloride.

[0027] According to the present invention, the titanium-containing compound can be selected from a wide range. In a preferred embodiment of the present invention, the organoaluminum compound has the general formula AlR. n X 3-n AlR n X 3-n R is a hydrogen group or a C1-C group. 20 The hydrocarbon group, where X is a halogen and n is 0, 1, 2, or 3. Preferably, at least one of trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, trioctylaluminum, diethylaluminum chloride, diisobutylaluminum chloride, and diethylaluminum chloride is selected.

[0028] According to the present invention, the molar ratio of the ether compound to the fluorinated ester compound in the electron donor can be selected within a wide range. In a preferred embodiment of the present invention, the molar ratio of the ether compound to the fluorinated ester compound in the electron donor is 1:99 to 99:1, preferably 10:90 to 60:40. That is, in molar terms, with 100 parts of the total amount of the ether compound and the fluorinated ester compound, the content (amount) of the ether compound is 1-99 parts, preferably 10-60 parts, for example, 10, 20, 30, 40, 50, 60 parts, or any two values ​​or any range of any two values; the content (amount) of the fluorinated ester compound is 1-99 parts, preferably 40-90 parts, for example, 90, 80, 70, 60, 50, 40 parts, or any two values ​​or any range of any two values.

[0029] According to the present invention, the proportions of the fluorinated ester electron-donating catalyst components can be selected within a wide range. In a preferred embodiment of the present invention, based on the total mass of the fluorinated ester electron-donating catalyst components as 100%, the content of Ti in the fluorinated ester electron-donating catalyst components is 0.3-7.0 wt%, the content of Mg is 9.0-21.0 wt%, the content of Al is 0-5.0 wt%, and the total mass of ether compounds and fluorinated ester compounds is 1.0-30.0 wt%. Preferably, the balance mainly includes Cl and alkoxy groups formed by the loss of H atoms from lower alcohols in magnesium alkoxide compounds, accounting for 40.0-70.0 wt%. Preferably, based on the total mass of the fluorinated ester electron-donating catalyst component as 100%, the content of Ti in the fluorinated ester electron-donating catalyst component is 1.5-4.0 wt%, the content of Mg is 13.0-17.0 wt%, the content of Al is 0-3.5 wt%, and the total mass of ether compounds and fluorinated ester compounds is 9.0-20.0 wt%, for example 9 wt%, 11 wt%, 13 wt%, 15 wt%, 17 wt%, 19 wt%, 20 wt%, and any two values ​​or any range of any two values; preferably, the balance mainly includes Cl element and alkoxy groups formed by the loss of H atoms from lower alcohols in magnesium alkoxide compounds, accounting for 46.0-60.0 wt%.

[0030] In a preferred embodiment of the present invention, the polymer powder synthesized using the fluorinated ester electron donor catalyst has a distribution of 55wt%-66wt% for particles <20 mesh, 31wt%-44wt% for particles 20-100 mesh, and no more than 0.5wt% for particles >200 mesh. The catalyst components of the present invention have regular particle shapes, are not easily broken, and result in less polymer powder.

[0031] A second aspect of the present invention is to provide a method for preparing a fluorinated ester electron donor catalyst component according to the first aspect, comprising chemically de-alcoholizing magnesium alkoxide particles derived from and / or those not physically de-alcoholized as a support, mixing the magnesium alkoxide support in an optional stage of the chemical de-alcoholization process with the electron donor and a titanium chloride, loading the electron donor and / or the titanium chloride onto the magnesium alkoxide support to obtain the fluorinated ester electron donor catalyst component.

[0032] According to the present invention, the magnesium alkoxide support comprises magnesium alkoxide particles that have not undergone physical de-alcoholization and magnesium alkoxide particles that have undergone physical de-alcoholization. The molar ratio of alcohol to magnesium in the magnesium alkoxide particles that have not undergone physical de-alcoholization is (2.0-3.6):1. The physical de-alcoholization method preferably employs hot nitrogen purging and / or vacuum de-alcoholization, with a molar ratio of alcohol to magnesium of (0.2-3.6):1, preferably a magnesium alkoxide support with a molar ratio of alcohol to magnesium in the range of (0.9-3.6):1. Preferably, the temperature of the physical de-alcoholization is 90℃-260℃, and the heating time is 3-6 hours. By changing the heat treatment temperature, the size of the catalyst particles can be easily adjusted and controlled.

[0033] In this invention, the magnesium alkoxide carrier can be derived from magnesium alkoxide particles that have undergone physical dealcoholization, or from magnesium alkoxide particles that have not undergone physical dealcoholization. Regardless of whether physical dealcoholization has been performed, a subsequent chemical dealcoholization step is required.

[0034] The spherical catalyst of the present invention is prepared according to the following method:

[0035] The first method involves using alkylaluminum to dealcoholize a magnesium alkoxide support to prepare a spherical catalyst: the spherical magnesium alkoxide support is dispersed in an inert solvent of saturated aliphatic hydrocarbons such as hexane, isobutane, heptane, cyclohexane, naphtha, hydrogenated gasoline, or kerosene, preferably hexane; then alkylaluminum is added for chemical dealcoholization; a titanium compound is added for titanium loading; and finally, an electron donor is added to prepare a spherical catalyst. Alternatively, the spherical support is dispersed in an inert solvent, and alkylaluminum and an electron donor are added sequentially, followed by titanium loading, to obtain a spherical catalyst.

[0036] The second method involves using titanium tetrachloride to prepare spherical catalysts by removing alcohol from a magnesium alkoxide support: Titanium tetrachloride is dispersed in a small amount of inert solvent, such as hexane, and the mixture is cooled before adding the magnesium alkoxide support. The temperature is then gradually increased. An electron donor is added, and the temperature is continued to rise. After reacting for a certain period of time, the mixture is filtered, and then a large amount of titanium tetrachloride is added to react. Finally, the mixture is washed multiple times with hexane until as much free titanium tetrachloride as possible is removed, yielding a spherical catalyst.

[0037] According to the present invention, the magnesium alkoxide carrier can be selected from a wide range. In a preferred embodiment of the present invention, the molar ratio of alcohol to magnesium in the magnesium alkoxide carrier is (0.2-3.6):1. After chemical de-alcoholization treatment, it is mixed with the titanium chloride compound and electron donor in an optional order of addition.

[0038] In a preferred embodiment of the present invention, the method for chemically de-alcoholizing the magnesium alkoxide support includes chemically de-alcoholizing the magnesium alkoxide support by mixing it with titanium chloride and optionally the organoaluminum compound; preferably, the magnesium alkoxide support is chemically de-alcoholized by alkylaluminum or titanium chloride, and then mixed with the electron donor and titanium chloride to obtain the fluorinated ester electron donor catalyst component.

[0039] According to the present invention, when the organoaluminum compound is used for chemical de-alcoholization, the preparation method can be adopted from the prior art. According to one preferred embodiment, the preparation method includes: dispersing a magnesium alkoxide compound support in an inert solvent (such as hexane), adding the organoaluminum compound at a temperature of -30 to 20°C, slowly heating to a temperature range of 20 to 60°C for chemical de-alcoholization for 0.5 to 4 hours, then adding the titanium-containing compound and mixing at 30 to 60°C for 0.5 to 4 hours to support titanium, and then mixing with the electron donor at 10 to 40°C for 0.2 to 3 hours to obtain the fluorinated ester electron donor catalyst component. According to another preferred embodiment, the preparation method involves dispersing a magnesium alkoxide support in an inert solvent (such as hexane), mixing it sequentially with the organoaluminum compound at 20-60°C for 0.5-4 h, mixing it with the electron donor at 10-40°C for 0.2-3 h, and finally mixing it with the titanium-containing compound at 30-60°C for 0.5-4 h to load titanium, thereby obtaining the fluorinated ester electron donor catalyst component.

[0040] According to the present invention, when the organoaluminum compound is used for chemical de-alcoholization, the ratio of each raw material can be selected within a wide range. In a preferred embodiment of the present invention, when the organoaluminum compound is used for chemical de-alcoholization, based on the mass of the magnesium alkoxide compound carrier as 1, the amount of the titanium-containing compound is 0.05-2, preferably 0.1-1, the amount of the organoaluminum compound is 0.01-5, preferably 0.05-2, and the total amount of electron donors of the fluorinated ester compound and the ether compound is 0.01-1, preferably 0.01-0.5; the molar ratio of the ether compound to the fluorinated ester compound in the electron donor is 1:99 to 99:1, preferably 10:90 to 60:40.

[0041] According to the present invention, when titanium tetrachloride is used for chemical dehydrogenation, the preparation method can be a method in the prior art. In a preferred embodiment of the present invention, when titanium tetrachloride is used for chemical dehydrogenation, the preparation method includes:

[0042] Titanium tetrachloride is dispersed in a small amount of inert solvent such as hexane, cooled to -40 to 0°C, and a magnesium alkoxide support is added. After 3-8 hours, the temperature is raised to 90-120°C, then lowered to 40-70°C, and the electron donor is added. The mixture is reacted at a constant temperature of 40-70°C for 0.5-4 hours. The mixture is then removed, and titanium tetrachloride is added again. The mixture is reacted at 30-60°C for 0.2-4 hours. Finally, the free titanium tetrachloride is removed to obtain the fluorinated ester electron donor catalyst component.

[0043] According to the present invention, when titanium tetrachloride is used for chemical de-alcoholization, the ratio of each raw material can be selected within a wide range. In a preferred embodiment of the present invention, based on the mass of the magnesium alkoxide carrier as 1, the amount of titanium tetrachloride is 10-200, preferably 30-60, and the total amount of electron donor is 0.01-1.0, preferably 0.01-0.5; the molar ratio of ether compounds to fluorinated ester compounds in the electron donor is 1:99-99:1, preferably 10:90-60:40.

[0044] A third aspect of the present invention is to provide a fluorinated ester-based electron-donating catalyst for ethylene polymerization, comprising the following components:

[0045] (1) The fluorinated ester electron donor catalyst component described in the first aspect and / or the fluorinated ester electron donor catalyst component prepared by the preparation method described in the second aspect;

[0046] (2) Alkyl aluminum, wherein the general formula of the alkyl aluminum is AlR n X 3-n AlR n X 3-n In this compound, R is hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, X is a halogen, preferably chlorine and / or bromine, and n is 1, 2, or 3; specific compounds include trimethylaluminum, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, trioctylaluminum, diethylaluminum chloride, diisobutylaluminum chloride, and diethylaluminum chloride. Triethylaluminum is preferred.

[0047] The molar ratio of aluminum in component (2) to titanium in component (1) is 5-500, preferably 20-200.

[0048] A fourth aspect of the present invention is to provide a fluorinated ester-based electron-donating catalyst component as described in the first aspect, a fluorinated ester-based electron-donating catalyst component prepared by the preparation method described in the second aspect, and the application of the fluorinated ester-based electron-donating catalyst as described in the third aspect in olefin polymerization reactions; preferably,

[0049] The polymerization process includes slurry polymerization and / or gas-phase polymerization; and / or, the olefin polymerization includes ethylene homopolymerization and copolymerization of ethylene and α-olefins.

[0050] The catalyst system described in this invention is suitable for the homopolymerization of ethylene and the copolymerization of ethylene with α-olefins. The α-olefin comonomers used include propylene, butene, hexene, and octene.

[0051] The catalyst system described in this invention can be used in different polymerization processes, including slurry polymerization and gas-phase polymerization.

[0052] Liquid-phase polymerization media include inert solvents such as hexane, cyclohexane, isobutane, heptane, benzene, toluene, xylene, naphtha, hydrogenated gasoline, and other saturated aliphatic hydrocarbons or aromatic hydrocarbons.

[0053] According to the above technical solution, the catalyst of this invention uses a novel blend of fluorinated ester compounds and common ether compounds as electron donors, combined with other specific raw materials mentioned in this application, unexpectedly yielding a spherical catalyst with uniform particle size, high activity, excellent hydrogen regulation performance, and good copolymerization performance. The resulting polymer exhibits spherical particles with very few fine particles, resulting in a lower polymer density. The catalyst of this invention, while maintaining high catalytic activity and advantages such as high spherical particle size and narrow particle size distribution of the polymer powder, significantly improves the copolymerization performance of the catalyst, providing a novel catalyst for the production of high-end grades such as low-density or ultra-low-density polyethylene resin. Therefore, the catalyst components and catalyst of this invention have significant application value.

[0054] Through research and verification, the inventors of this invention believe that the catalyst of this invention possesses the aforementioned advantages because the strong electron-withdrawing effect of fluorine atoms significantly alters the electron cloud density of the catalyst's active center. Compared to other halogen ester compounds, the introduction of fluorine atoms maximizes the electron-withdrawing effect, greatly reducing the electron cloud density of the catalytic center, thereby regulating the copolymerization performance of the catalyst. Combined with other specific components in this invention, an ethylene gas-phase polymerization catalyst with good copolymerization performance, uniform particle size, and narrow particle size distribution is obtained. Detailed Implementation

[0055] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0056] In the following embodiments, the following methods are used for detection:

[0057] 1. Detection methods for components of spherical catalysts: Inductively coupled plasma atomic emission spectrometry (ICP) and nuclear magnetic resonance (NMR). Metal elements can be directly detected by ICP, and electron donors can be directly detected by NMR.

[0058] 2. The method for detecting the catalytic activity of spherical catalysts is: divide the mass of polymer powder by the mass of catalyst;

[0059] 3. The test method for the bulk density (BD) of polymer powder is DIN-53194.

[0060] 4. The method for detecting the density of polymer powder is the density tube method.

[0061] 5. The method for detecting polymer particle size distribution is: MASTERSIZE particle size analyzer.

[0062] Preparation of spherical catalyst components

[0063] Example 1

[0064] In a 250 mL reactor thoroughly purged with high-purity nitrogen, 6.0 g of spherical magnesium ethanol chloride support (molecular ratio of ethanol to magnesium chloride 2.6) was added sequentially (the synthesis of the magnesium ethanol chloride support is described in patent CN93102795.0A), along with 120 mL of hexane. The mixture was stirred and cooled to 0 °C. 10 mL of a 1 M triethylaluminum solution in hexane was added dropwise, and the mixture was heated to 35 °C and reacted for 2 hours. 4 mL of titanium tetrachloride was added, and the mixture was heated to 60 °C and reacted for 2 hours. The system was then hot-washed three times and cold-washed once. The system was cooled to 20 °C, and 1 mL of a tetrahydrofuran and trifluoroethyl acetate solution in hexane was added (volume ratio of tetrahydrofuran, trifluoroethyl acetate, and hexane 0.35:0.65:10). The mixture was reacted at 20 °C for 0.5 hours. The filtrate was filtered, washed twice with hexane, and the solid was dried with nitrogen to obtain a highly free-flowing spherical catalyst component.

[0065] Example 2

[0066] In a 250 mL reactor thoroughly purged with high-purity nitrogen, 6.0 g of spherical magnesium ethanol chloride support (molecular ratio of ethanol to magnesium chloride 2.6), 120 mL of hexane, and the mixture was stirred and cooled to 0 °C. 10 mL of a 1 M triethylaluminum solution in hexane was added dropwise, and the mixture was heated to 35 °C and reacted for 2 hours. After washing three times with hexane, 1 mL of a tetrahydrofuran and trifluoroethyl acetate solution in hexane (volume ratio of tetrahydrofuran, trifluoroethyl acetate, and hexane 0.35:0.65:10) was added, and the mixture was reacted at a constant temperature of 20 °C for 0.5 hours. Then, 4 mL of titanium tetrachloride was added, and the mixture was heated to 60 °C and reacted for 2 hours. The system was then hot-washed three times and cold-washed once. The system was cooled to 20 °C, the filtrate was filtered, washed twice with hexane, and the solid was dried with nitrogen to obtain a highly free-flowing spherical catalyst component.

[0067] Example 3

[0068] In a 250 mL reactor that had been fully purged with high-purity nitrogen, 90 mL of titanium tetrachloride and 7 mL of hexane were added. The mixture was cooled to -20 °C, and 6.0 g of spherical magnesium ethanol chloride support (molecular ratio of ethanol to magnesium chloride was 2.6) was added. The mixture was reacted at -20 °C for 0.5 h, and then the temperature was programmed to rise from -20 °C to 110 °C over 4 h. The mixture was kept at this temperature for 0.5 h, cooled to 60 °C, and 1 mL of a hexane solution of tetrahydrofuran and ethyl trifluoroacetate (volume ratio of tetrahydrofuran, ethyl trifluoroacetate, and hexane was 0.35:0.65:10) was added. The mixture was kept at 60 °C for 2 h, cooled to room temperature, washed twice with hexane to remove the mixture, and then 40 mL of titanium tetrachloride was added. The mixture was reacted at 45 °C for 2 h, cooled to 20 °C, and the filtrate was filtered out. The mixture was washed six times with hexane, and the solid was dried with nitrogen to obtain a spherical catalyst component with good flowability.

[0069] Example 4

[0070] The catalyst synthesis steps were the same as in Example 1, with the only variable being that 6.0 g of spherical magnesium ethanol chloride support (molecular ratio of ethanol to magnesium chloride was 2.6) was replaced with 6.0 g of spherical magnesium ethanol chloride support obtained by physical de-alcoholization (molecular ratio of ethanol to magnesium chloride was 1.4).

[0071] Example 5

[0072] The catalyst synthesis steps were the same as in Example 1, with the only variable being that the electron donor, ethyl trifluoroacetate, was replaced with ethyl 2-(3,4-difluorophenyl)-2,2-difluoroacetate.

[0073] Example 6

[0074] The catalyst synthesis steps were the same as in Example 1, with the only variable being that the electron donor, ethyl trifluoroacetate, was replaced with ethyl pentafluorobenzoate.

[0075] Example 7

[0076] The catalyst synthesis steps were the same as in Example 1, with the only variable being that the electron donor, ethyl trifluoroacetate, was replaced with ethyl 2,2,2-trifluoroacetate.

[0077] Example 8

[0078] The catalyst synthesis steps were the same as in Example 1, with the only variable being that the magnesium alkoxide support with a magnesium alkoxide molar ratio of 2.6 was replaced with a magnesium alkoxide support with a magnesium alkoxide molar ratio of 0.9.

[0079] Comparative Example 1

[0080] The catalyst synthesis steps were the same as in Example 1, with the only variable being that the electron donor, ethyl trifluoroacetate, was replaced with ethyl acetate.

[0081] Comparative Example 2

[0082] The catalyst synthesis steps were the same as in Example 1, with the only variable being that the hexane solution of tetrahydrofuran and ethyl trifluoroacetate was replaced with the hexane solution of ethyl trifluoroacetate, and tetrahydrofuran was not added to the system.

[0083] Ethylene polymerization

[0084] The 2L stainless steel reactor was purged three times each with nitrogen and ethylene to fully replace the system atmosphere. Then, 1L of dried hexane was added sequentially, followed by a certain amount of liquid hexene (5mL, 15mL, or 30mL, see Table 2 for details), 1.0mL of 1M triethylaluminum in hexane, and a hexane suspension of the spherical catalyst component (containing 0.6mg of titanium) prepared above. The temperature was raised to 75℃, hydrogen gas was introduced at a pressure of 0.28MPa, and then ethylene gas was introduced at a partial pressure of 0.75MPa, maintaining the total system pressure at 1.03MPa. Polymerization was carried out at 85℃ for 2 hours. After the polymerization reaction was completed, the polyethylene granules were collected.

[0085] Spherical catalyst components and polymerization properties of the catalyst

[0086] Table 1: Components of spherical catalysts

[0087]

[0088] In Table 1, the contents of Ti, Mg, Al, and electron donors (based on the total mass of ether compounds and fluorinated ester compounds) are listed, with the total mass of the spherical catalyst in each embodiment being 100%. The remainder is the remaining components of the catalyst, which mainly include Cl atoms and alkoxy groups formed by the loss of H atoms from the lower alcohols in the magnesium alkoxide support.

[0089] Table 2: Catalytic performance of spherical catalysts

[0090]

[0091] Polymerization conditions: Polymerization temperature: 85℃, polymerization time: 2 hours, hydrogen / ethylene partial pressure: 0.28 / 0.75 MPa respectively. BD refers to the bulk density of the polymer powder.

[0092] Note 1: When using the catalyst of Example 1, the amount of hexene exceeded 30 mL, resulting in stickiness in the polymerization reactor and some powder adhering to the reactor wall. Note 2: When using the catalyst of Comparative Example 1, the amount of hexene was 30 mL, resulting in stickiness in the polymerization reactor and some powder adhering to the reactor wall. Furthermore, the obtained polymer was mainly in block form, and the sieve analysis data was distorted, so it is not shown in the table.

[0093] As shown in Table 1, the spherical catalyst of this invention exhibits good copolymerization performance in ethylene polymerization. Under the same conditions, the fluorinated ester compounds, as electron donors, catalyze the copolymerization of ethylene and hexene, resulting in a lower polymer powder density. Furthermore, when the amount of hexene is 30 mL, the fluorinated ester compounds catalyze the copolymerization of ethylene and are less prone to sticking to the reactor compared to the comparative catalyst, indicating that the copolymerization performance of the catalyst is superior to that of the comparative catalyst.

[0094] In this field, provided the catalyst does not break during polymerization, the shape of the polymer powder is the same as that of the catalyst, i.e., the metamorphic effect. As can be seen from the particle size distribution of the polymer in Table 1, there are very few fine particles in the polymer powder, and the resulting polymer exhibits spherical particles. This also verifies that the catalyst in this invention maintains almost the entire support during the synthesis process, and the resulting catalyst has the characteristics of uniform particle size and narrow particle size distribution.

[0095] In summary, the catalyst of this invention utilizes a novel blend of fluorinated esters and common ethers as electron donors, combined with other specific raw materials described in this application, unexpectedly yielding a spherical catalyst with uniform particle size, high activity, hydrogen-modulated properties, and excellent copolymerization performance. The resulting polymer exhibits spherical particles with minimal fine division, resulting in a lower density polymer. The catalyst of this invention, while maintaining high catalytic activity and the advantages of high spherical particle size and narrow particle size distribution of the polymer powder, significantly improves the copolymerization performance of the catalyst, providing a novel catalyst for the production of high-end grades such as low-density or ultra-low-density polyethylene resin. Therefore, the catalyst components and catalyst of this invention have significant potential for widespread application.

[0096] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.

[0097] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In case of conflict, the definitions in this specification shall prevail.

[0098] When this specification uses the prefixes “known to those skilled in the art,” “prior art,” or similar terms to derive materials, substances, methods, steps, apparatus, or components, the objects derived from such prefixes cover those commonly used in the art at the time of this application’s filing, but also include those that are not currently commonly used but will become generally recognized in the art as suitable for similar purposes.

[0099] The endpoints and any values ​​of the ranges disclosed in this application are not limited to the precise ranges or values; such ranges or values ​​should be understood to include values ​​close to them. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In principle, various technical solutions can be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.

[0100] In the context of this specification, except where expressly stated otherwise, any matters or issues not mentioned shall apply directly to those known in the art without any modification.

[0101] Furthermore, any implementation described herein can be freely combined with one or more other implementations described herein, and the resulting technical solutions or technical ideas shall be regarded as part of the original disclosure or original record of the present invention, and should not be regarded as new content not disclosed or anticipated herein, unless those skilled in the art consider the combination to be obviously unreasonable.

Claims

1. A fluorinated ester-based electron donor catalyst component comprising the reaction products of the following components: ① a support, wherein the support is a magnesium alkoxide compound; ② a titanium-containing compound; optionally ③ an organoaluminum compound; ④ an electron donor, wherein the electron donor comprises an ether compound and a fluorinated ester compound.

2. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The ether compounds are shown in formula (1): Formula (1); in Formula (1), R1 and R2 are unsubstituted C1-C14 aliphatic hydrocarbon groups or aromatic hydrocarbon groups; or, R1 and R2 are linked together to form cyclic ethers and their derivatives.

3. The fluorinated ester-based electron-donating catalyst component according to claim 2, characterized in that: The ether compounds are monoether compounds.

4. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The ether compound is at least one of the following: methyl ether, diethyl ether, n-propyl ether, isopropyl ether, n-butyl ether, methyl ethyl ether, methyl butyl ether, ethyl isopropyl ether, ethyl butyl ether, ethylene oxide, 1,2-epoxypropane, 1,2-epoxybutane, 2,3-epoxybutane, tetrahydrofuran, anisole, diphenyl ether, phenethyl ether, benzyl ether, benzyl methyl ether, benzyl ethyl ether, benzyl phenyl ether, and cyclopentane oxide.

5. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The fluorinated ester compounds include simple fluorinated ester compounds and / or fluorinated ester compounds in which fluorine is substituted with other elements.

6. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The fluoroester compounds include at least one of the following compounds: Fluorinated esters represented by formula (2), aromatic fluorinated esters represented by formula (3), and fluoroalkyl acid esters represented by formula (4) and / or formula (5); Formula (2), in which groups R1 and R2 are the same or different, and are respectively H, F, Cl, Br, I, substituted or unsubstituted phenyl, C1-C 14 Alkyl or fluoroalkyl; R3 is C1-C 14 Aliphatic or aromatic hydrocarbon groups; In equation (3), R1, R2, R3, R4, and R5 are respectively H, F, Cl, Br, I, CF3, NH2, NO2, CN, or Cl-C. 14 The alkyl group, wherein at least one of R1, R2, R3, R4, and R5 is F or CF3; R6 is C1-C 14 Aliphatic or aromatic hydrocarbon groups; Equation (4) In formula (5), R1, R2, and R3 in formula (4) and formula (5) are each H, F, CH3, CF3, or one of alkyl, olefinic, or aromatic groups with fewer than 14 carbon atoms; In equations (4) and (5), R4 and R5 are respectively H, F, Cl, Br, I, CF3, and Cl-C. 14 Alkyl or halogen-substituted C1-C 14 Alkyl or aromatic groups.

7. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The magnesium alkoxide compound is in the form of spherical particles; and / or, The molar ratio of alcohol to magnesium in the magnesium alkoxide compound is (0.2-3.6):1; and / or, The alcohol in the magnesium alkoxide compound is a low-carbon alcohol of C1-C4; and / or, The magnesium source in the magnesium alkoxide compound is magnesium chloride.

8. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The alcohol in the magnesium alkoxide compound is at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.

9. The fluorinated ester-based electron-donating catalyst component according to claim 1, characterized in that: The titanium-containing compound has the general formula Ti(OR). n X 3-n Or Ti(OR) m X 4-m Ti(OR) n X 3-n And Ti(OR) m X 4-m In the formula, R may be the same or different, each being a C1-C14 aliphatic or aromatic hydrocarbon group, X is chlorine, 3-n and 4-m are positive integers and n and m are zero or positive integers; and / or, The general formula of the organoaluminum compound is AlR n X 3-n AlR n X 3-n R is hydrogen or C1-C 20 The hydrocarbon group, where X is a halogen and n is 1, 2, or 3.

10. The fluorinated ester-based electron-donating catalyst component according to any one of claims 1-9, characterized in that: The molar ratio of ether compounds to fluorinated ester compounds in the electron donor is 1:99 to 99:

1.

11. The fluorinated ester-based electron-donating catalyst component according to any one of claims 1-9, characterized in that: The molar ratio of ether compounds to fluorinated ester compounds in the electron donor is 10:90 to 60:

40.

12. The fluorinated ester-based electron-donating catalyst component according to any one of claims 1-9, characterized in that: Based on the total mass of the fluorinated ester electron donor catalyst component as 100%, the content of Ti element in the fluorinated ester electron donor catalyst component is 0.3-7.0 wt%, the content of Mg element is 9.0-21.0 wt%, the content of Al element is 0-5.0 wt%, and the total mass of ether compounds and fluorinated ester compounds is 1.0-30.0 wt%.

13. The fluorinated ester-based electron-donating catalyst component according to any one of claims 1-9, characterized in that: Based on the total mass of the fluorinated ester electron donor catalyst component as 100%, the content of Ti element in the fluorinated ester electron donor catalyst component is 1.5-4.0 wt%, the content of Mg element is 13.0-17.0 wt%, the content of Al element is 0-3.5 wt%, and the total mass of ether compounds and fluorinated ester compounds is 9.0-20.0 wt%.

14. The fluorinated ester-based electron-donating catalyst component according to any one of claims 1-9, characterized in that: The proportion of polymer powder synthesized using the fluorinated ester electron donor catalyst is 55wt%-66wt% for particles <20 mesh, 31wt%-44wt% for particles 20-100 mesh, and no more than 0.5wt% for particles >200 mesh.

15. A method for preparing a fluorinated ester electron donor catalyst component according to any one of claims 1-14, comprising chemically de-alcoholizing magnesium alkoxide particles derived from and / or those not physically de-alcoholized as a support, mixing the magnesium alkoxide support in an optional stage of the chemical de-alcoholization process with the electron donor and a titanium chloride, loading the electron donor and / or the titanium chloride onto the magnesium alkoxide support to obtain the fluorinated ester electron donor catalyst component.

16. The preparation method according to claim 15, characterized in that: The molar ratio of alcohol to magnesium in magnesium alkoxide particles without physical de-alcoholization is (2.0-3.6):1; and / or, the physical de-alcoholization method employs hot nitrogen purging and / or vacuum de-alcoholization, and the molar ratio of alcohol to magnesium after physical de-alcoholization is (0.2-3.6):1; And / or, the physical de-alcoholization temperature is 90℃-260℃, and the heating time is 3-6 hours.

17. The preparation method according to claim 15, characterized in that: The physical alcohol removal method employs hot nitrogen purging and / or vacuum alcohol removal, resulting in a molar ratio of alcohol to magnesium of (0.9-3.6):1 after physical alcohol removal.

18. The preparation method according to claim 15, characterized in that: The method for chemically removing alcohol from a magnesium alkoxide carrier includes chemically removing alcohol from a mixture of titanium chloride and, optionally, the organoaluminum compound, with the magnesium alkoxide carrier.

19. The preparation method according to claim 15, characterized in that: The magnesium alkoxide support is chemically de-alcoholized with alkyl aluminum or titanium chloride, and then mixed with the electron donor and titanium chloride to obtain the fluorinated ester electron donor catalyst component.

20. The preparation method according to claim 18, characterized in that: When titanium chloride and the organoaluminum compound are used for chemical de-alcoholization, the preparation method includes: The magnesium alkoxide compound support is dispersed in an inert solvent, and the organoaluminum compound is added at a temperature of -30 to 20°C. Chemical de-alcoholization is then carried out at a temperature range of 20 to 60°C for 0.5 to 4 hours. Next, the titanium chloride is added and mixed at 30 to 60°C for 0.5 to 4 hours to support the titanium. Afterward, it is mixed with the electron donor at 10 to 40°C for 0.2 to 3 hours to obtain the fluorinated ester electron donor catalyst component; or... The magnesium alkoxide support is dispersed in an inert solvent, and then mixed sequentially with the organoaluminum compound at 20-60°C for 0.5-4 h, with the electron donor at 10-40°C for 0.2-3 h, and finally with the titanium chloride at 30-60°C for 0.5-4 h to carry titanium, thereby obtaining the fluorinated ester electron donor catalyst component.

21. The preparation method according to claim 18, characterized in that: When using titanium chloride and the organoaluminum compound for chemical de-alcoholization, with the mass of the magnesium alkoxide compound carrier as 1, the amount of titanium chloride used is 0.05-2, the amount of the organoaluminum compound used is 0.01-5, and the total amount of electron donors of the fluorinated ester compound and ether compound is 0.01-1; the molar ratio of ether compound to fluorinated ester compound in the electron donor is 1:99~99:

1.

22. The preparation method according to claim 18, characterized in that: When using titanium chloride and the organoaluminum compound for chemical de-alcoholization, with the mass of the magnesium alkoxide compound carrier as 1, the amount of titanium chloride used is 0.1-1, the amount of the organoaluminum compound used is 0.05-2, and the total amount of electron donors of the fluorinated ester compound and ether compound is 0.01-0.5; the molar ratio of ether compound to fluorinated ester compound in the electron donor is 10:90~60:

40.

23. The preparation method according to claim 18, characterized in that: When titanium tetrachloride is used for chemical dehydrogenation, the preparation method includes: Titanium tetrachloride was dispersed in a small amount of inert solvent, cooled to -40 to 0°C, and a magnesium alkoxide support was added. The mixture was heated to 90-120°C over 3-8 hours, then cooled to 40-70°C, and the electron donor was added. The reaction was carried out at 40-70°C for 0.5-4 hours. The mixture was removed, and titanium tetrachloride was added again, reacting at 30-60°C for 0.2-4 hours. Finally, the free titanium tetrachloride was removed to obtain the fluorinated ester electron donor catalyst component; and / or, With the mass of the magnesium alkoxide compound carrier as 1, the amount of titanium tetrachloride is 10-200, and the total amount of electron donor is 0.01-1.0; the molar ratio of ether compound to fluorinated ester compound in the electron donor is 1:99~99:

1.

24. The preparation method according to claim 18, characterized in that: When titanium tetrachloride is used for chemical dehydrogenation, the preparation method includes: With the mass of the magnesium alkoxide compound carrier as 1, the amount of titanium tetrachloride is 30-60, and the total amount of electron donor is 0.01-0.5; the molar ratio of ether compound to fluorinated ester compound in the electron donor is 10:90~60:

40.

25. A fluorinated ester-based electron donor catalyst for ethylene polymerization, comprising the following components: (1) The fluorinated ester electron donor catalyst component according to any one of claims 1-14 and / or the fluorinated ester electron donor catalyst component prepared by the preparation method according to any one of claims 15-24; (2) Alkyl aluminum, wherein the general formula of the alkyl aluminum is AlR n X 3-n AlR n X 3-n In this case, R represents hydrogen or a hydrocarbon group with 1 to 20 carbon atoms, and X represents a halogen. The molar ratio of aluminum in component (2) to titanium in component (1) is 5-500.

26. The fluorinated ester-based electron-donating catalyst according to claim 25, characterized in that: The general formula of the alkylaluminum is AlR n X 3-n AlR n X 3-n In this system, R represents hydrogen or a hydrocarbon group with 1 to 20 carbon atoms, X represents chlorine and / or bromine, and n represents 1, 2, or 3.

27. The fluorinated ester-based electron-donating catalyst according to claim 25, characterized in that: The molar ratio of aluminum in component (2) to titanium in component (1) is 20-200.

28. The application of a fluorinated ester electron donor catalyst component according to any one of claims 1-14, a fluorinated ester electron donor catalyst component prepared by the preparation method according to any one of claims 15-24, and a fluorinated ester electron donor catalyst according to any one of claims 25-27 in olefin polymerization reactions.

29. The application according to claim 28, characterized in that: The polymerization process includes slurry polymerization and / or gas-phase polymerization; and / or, the olefin polymerization includes ethylene homopolymerization and copolymerization of ethylene and α-olefins.

Citation Information

Patent Citations

  • Catalyst component preparation method and catalyst for vinyl polymerization

    CN102020732A

  • Preparation method of catalyst component for polymerization of vinyl and catalyst for polymerization of vinyl

    CN102050897B

  • Spherical catalyst for olefinic polymerization

    CN1091748A

  • Highly active catalyst for polymerization of olefins and method for the preparation of the same

    CN1099041A

  • Catalyst for polymerization or copolymerization of ethylene and its producing process and application

    CN1118488C